Urban Signal Propagation Study Using Ray Tracing Methods in Tegucigalpa, Honduras - Sosa Fernández, Andrea Nicolle; Silva, Rolando Arturo (LACCEI, 2024)
Ray tracing function plays a crucial role in urban signaling, expanding its application from multipath propagation to the detailed analysis of different signal paths in urban environments. This study focuses on the comprehensive exploration of coverage analysis and the adaptation of building structures in the mountainous region of Central America, specifically in Tegucigalpa, Honduras. The goal is to improve accuracy in predicting radio frequency coverage and signal quality in the region. The electromagnetic analysis is considered, contributing to loss calculations using the Fresnel equation, the Uniform Diffraction Theory, geometric angle, and the permittivity of building materials. A key innovation in this research is the integration of ray tracing algorithm with Shooting and Bouncing Ray (SBR) and the Image Method. Emitting rays in various directions enables a holistic understanding of signal propagation across multiple paths within urban environments. The model titled 'Urban Link and Coverage Analysis Using Ray Tracing' provides the fundamental framework for this analysis, showing significant potential to streamline the estimated time required to design communication networks in urban areas. Furthermore, the use of multiple signal paths in urban environments offers a crucial advantage to enhance signal robustness and reliability.